KISS1R and ANKRD31 Cooperate to Enhance Leydig Cell Gene Expression via the Cytoskeletal-Nucleoskeletal Pathway - Ricci, Giulia; Guillou, Florian; Catizone, Angela; Mele, Vincenza Grazia; Moggio, Martina; Chioccarelli, Teresa; Diano, Nadia; Meccariello, Rosaria; Pierantoni, Riccardo; Fasano, Silvia; Cobellis, Gilda; Chianese, Rosanna; et al. (Frontiers in Cell and Developmental Biology, 2022)
Kisspeptins are involved in the regulation of hypothalamic-pituitary-gonadal axis, Leydig cell functions and testosterone secretion, acting as endogenous ligands of KISS1 receptor. ANKRD31 protein participates in male fertility, regulating meiotic progression and epididymal sperm maturation. Here we show that, in Leydig cells, KISS1 receptor and ANKRD31 proteins physically interact; the formation of this protein complex is enhanced by Kisspeptin-10 that also modulates F-ACTIN synthesis, favoring histone acetylation in chromatin and gene expression via cytoskeletal-nucleoskeletal pathway. The deregulation of Kp/KISS1R system, the expression impairment of cytoskeletal-nucleoskeletal mediators, as well as of Leydig gene targets, and the decreased testosterone secretion in Ankrd31-/- testis strongly supported our hypothesis. Furthermore, Cytochalasin-D treatment subverted the gene expression induction dependent on Kisspeptin-10 action. In conclusion, the current work highlights a novel role for the Kisspeptin-10 in the induction of the cytoskeletal-nucleoskeletal route, downstream a physical interaction between KISS1 receptor and ANKRD31, with gene expression activation as final effect, in Leydig cells.